Nutrition for developing countries - Savage King, F. (Felicity), 1939-; Burgess, Ann. (Oxford : Oxford University Press, 1993)
The authors explain in clear simple language and practical detail how nutrition workers can help families with nutrition problems, how to treat malnourished children, and how to work in communities and schools.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nutrition; Nutrition -- Developing countries